Ocenění výše škody způsobené pádem stromu na rekreační chatu v Roudné u Nových Hradů - Šoula, Michal (Vysoké učení technické v Brně. Ústav soudního inženýrství, 2016)
Cílem této diplomové práce je stanovení výše pojistného plnění za totální škodu vzniklou pádem stromu při vichřici na rekreační chatu v Roudné u Nových Hradů. V teoretické části jsou řešeny základní pojmy z oblasti pojišťovnictví a základní pojmy a metody z oblasti oceňování nemovitých věcí. V praktické části je popsán původní stav objektu a ocenění objektu před pojistnou událostí nákladovou metodou dle oceňovací vyhlášky. Dále se tato práce věnuje stanovení nákladů položkovým rozpočtem, pro uvedení objektu do původního stavu. V závěru práce je vyhodnocen vliv rekonstrukce na výši pojistného plnění.

The aim of this thesis is to determine the amount of indemnity for total damage caused by a falling tree during the gale on a cottage in Roudné near Nové Hrady. The theoretical part deals with basic insurance terminology and basic terminology and methods used in property evaluation. The practical part describes the original condition of the property and its evaluation before the insured event using a cost method and complying with the evaluation regulation. Furthermore, this thesis deals with determination of the costs through the itemized budget for bringing the property to its original state. The conclusion deals with the impact of reconstruction on the extent of indemnity.
Valuation of the damage by fallen tree to a recreation cottage in Roudná u Nových Hradů
Keywords: Pojistná událost; pojistná smlouva; oceňování nemovitých věcí; vichřice; pád stromu; chata; totální škoda; cena nová; nákladová metoda; položkový rozpočet.; An insured event; an insurance contract; property evaluation; the gale; a tree fall; a cottage; total damage; a new price; a cost method; an itemized budget.